Multifunctional lignin-poly (lactic acid) biocomposites for packaging applications - Esakkimuthu, Esakkiammal Sudha; DeVallance, David; Pylypchuk, Ievgen; Moreno, Adrian; Sipponen, Mika H. (Frontiers in Bioengineering and Biotechnology, 2022)
Lignin is the most abundant aromatic biopolymer with many promising features but also shortcomings as a filler in polymer blends. The main objective of this work was to improve the processability and compatibility of lignin with poly(lactic acid) (PLA) through etherification of lignin. Commercial kraft lignin (KL) and oxypropylated kraft lignin (OPKL) were blended with PLA at different weight percentages (1%, 5%, 10%, 20% and 40%) followed by injection molding. Low lignin contents between 1% and 10% generally had a favorable impact on mechanical strength and moduli as well as functional properties of the PLA-based composites. Unmodified lignin with free phenolic hydroxyl groups rendered the composites with antioxidant activity, as measured by radical scavenging and lipid peroxidation tests. Incorporating 5% to 10% of KL or OPKL improved the thermal stability of the composites within the 300–350 ⁰C region. DSC analysis showed that the glass transition temperature values were systematically decreased upon addition of KL and OPKL into PLA polymer. However, low lignin contents of 1% and 5% decreased the cold crystallization temperature. The composites of KL and OPKL with PLA exhibited good stabilities in the migration test, with values of 17 mg kg-1 and 23 mg kg-1 even at higher lignin content 40%, i.e., well below European standard (60 mg kg-1). These results suggest oxypropylated lignin as a functional filler in PLA for safe and functional food packaging and antioxidant applications.